Mechanism and application of yeast and its culture in regulating intestinal antioxidant defense in ruminants - Yang, Lan; Wu, Xiaoxuan; Liu, Dacheng (Frontiers in Veterinary Science, 2025)
In intensive farming mode, oxidative stress is caused by excessive production of reactive oxygen species in ruminants, which seriously threaten animal health and production performance by disrupting intestinal barrier integrity, damaging nutritional metabolism, and inducing inflammatory reactions. Research indicates that yeast supplementation can enhance ruminant health and production performance, while alleviating oxidative stress. Compared to traditional synthetic antioxidants, yeast and its cultures have emerged as preferred solutions due to their multi-target regulatory actions and inherent biosafety. This article focuses on ruminants and integrates recent research findings to systematically review the mechanisms underlying oxidative stress responses in animal organisms, the antioxidant defense system of animals, and the role of yeast and its cultures in enhancing animal antioxidant capacity, to provide ideas for analyzing effective strategies for regulating animal oxidative stress response.